ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIK USAHA KECIL MENENGAH DALAM PELAPORAN KEWAJIBAN PERPAJAKAN DI DAERAH KOTA BIMA ( Studi kasus UMKM berada di kota bima ) - Imelda Imelda; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study is to analyze the effect of taxpayer knowledge, understanding of taxpayers, benefits perceived by taxpayers, and optimistic attitude of taxpayers on taxpayer reporting. Analyzing the influence of taxpayer knowledge on tax liability reporting. Analyzing the influence of taxpayer understanding on tax liability reporting. Analyzing the influence of taxpayer interest perceptions on tax liability reporting. Analyzing the effect of taxpayer optimism on tax liability reporting. The population in this study are micro business taxpayers. Small and Medium Enterprises (UMKM) registered at the Bima City Tax Service Office (KPP). The sampling technique for this research is purposive sampling method, namely: sampling using the criteria that the members of the population who become the sample are MSMEs registered at the Tax Office (KPP) in Bima City. The sample in this study were 64 respondents. In conducting data analysis using multiple linear regression with variables of taxpayer knowledge, understanding of taxpayers, perceived benefits of taxpayers, optimistic attitude of taxpayers as independent variables. the variable tax liability reporting as the dependent variable. Based on the simultaneous calculation or testing, it shows that the taxpayer's knowledge, understanding of the taxpayer, the benefits felt by the taxpayer, the taxpayer's optimistic attitude jointly affect the reporting of tax obligations.keywords: tax liability reporting, taxpayer knowledge, taxpayer understanding, benefits felt by taxpayers, taxpayer optimism.